Nature-pandemic relationships from the complex adaptive systems standpoint - Arce Rojas, Rodrigo (2021)
This article aims to take out guidelines for addressing future pandemics from the recognition of the close relationship between nature and society through the application of the complex adaptive systems approach. From the review, it is concluded that the adoption of the complex adaptive systems approach allows assuming the complexity paradigm when addressing pandemics, reinforcing the reductionist systems approaches that, while it is true that they respond in cause and effect linear situations, they have limitations when facing phenomena with the characteristics of complexity: self-organization (emergency), non-linearity (chaos), adaptation-evolution (cybernetics) and interconnectivity (network structure), among others. From the approach of the complex adaptive systems and the socio-ecological systems, it is possible to understand the close interrelationships and interdependencies between the ecological subsystem and the social subsystem, thus better understanding the relationships between nature and pandemic as part of a larger relationships network.